Faecal Biomarkers in Inflammatory Bowel Diseases: Calprotectin Versus Lipocalin-2—a Comparative Study. (18th June 2020) - Zollner, Andreas; Schmiderer, Andreas; Reider, Simon J; Oberhuber, Georg; Pfister, Alexandra; Texler, Bernhard; Watschinger, Christina; Koch, Robert; Effenberger, Maria; Raine, Tim; Tilg, Herbert; Moschen, Alexander R
Abstract: Background and Aims: Faecal biomarkers, particularly calprotectin [FCAL], have become important diagnostic and monitoring tools in inflammatory bowel diseases [IBD]. As FCAL is mainly produced by neutrophils, we hypothesised that faecal lipocalin-2 [FLCN2], also expressed by intestinal epithelial cells [IEC], could be beneficial in specific clinical situations. Methods: We compared clinical and endoscopic activity-related correlations between FCAL and FLCN2, assayed from the same sample, in a cohort of 132 patients (72 Crohn's disease [CD]) and 40 controls. A detailed analysis of cellular origins was done by confocal microscopy and flow cytometry. To evaluate the potential to detect low-grade inflammation, we studied faecal and tissue concentrations in a cohort with clinical, endoscopic, and histological remission. Results: There was an excellent correlation between FCAL and FLCN2 [rS = 0.87, p <0.001] and comparable sensitivity and specificity to predict clinical and endoscopic disease activity, with optimal thresholds for endoscopic activity of 73.4 and 1.98 µg/g in ulcerative colitis [UC] and 78.4 and 0.56 µg/g in Crohn's disease for FCAL and FLCN2, respectively. Strong co-expression of both proteins was observed in granulocytes and macrophages. IECs expressed LCN2 but not CAL. In our IBD cohort in deep remission neither FCAL nor FLCN2 was different from controls; yet mucosal LCN2 but not CAL expressions remained elevated in the rectum of UC and the ileum of CD patients. Conclusions: This study corroborates the diagnostic equivalence of FLCN2 and FCAL in IBD. In remission, persistent mucosal overexpression renders LCN2 an attractive candidate for molecular inflammation warranting further investigation.